Insights on the formation of the Warrego Au-Cu-Bi deposit from monazite and xenotime U-Pb dating: A new mineralization event in the Tennant Creek province - Damian Braize; Jeffrey A. Steadman; Sebastien Meffre; Pablo Farias (Precambrian Research, 2026)

Early Paleozoic magmatism and Au mineralization in the central Truong Son Belt: Insights from geochronology and lead isotope at the Me Xi gold deposit, Vietnam - Truong Xuan Le; Khin Zaw; Hai Thanh Tran; Sebastien Meffre; Pham Trung Hieu; Nguyen Dinh Luyen; Luong Quang Khang; Dinh Trong Tuong (Journal of Asian Earth Sciences, 2026)

Correction: Practical Application of Geophysical Methods for Characterisation of Waste Rock Dumps - Christopher C. Allen; Matthew J. Cracknell; Clare B. Miller; Owen P. Missen; Sebastien Meffre (Mine Water and the Environment, 2026)

Practical Application of Geophysical Methods for Characterisation of Waste Rock Dumps - Christopher C. Allen; Matthew J. Cracknell; Clare B. Miller; Owen P. Missen; Sebastien Meffre (Mine Water and the Environment, 2026)

Co-disposal of wood ashes and mine wastes to control acid and metalliferous drainage - Annah Moyo; Anita Parbhakar-Fox; Sebastien Meffre; David R. Cooke (Environmental Research, 2025)

Multi-mineral geochronology reveals a protracted Mesoproterozoic tectonic and metallogenic link between southeastern Australia and Laurentia - Sheree Armistead; Sebastien Meffre; Ralph Bottrill; Andrew Cross; David Huston; Grace Cumming (Precambrian Research, 2024)

Using compositions of zircon to reveal fertile magmas for the formation of porphyry deposits in the Loei and Truong Son fold belts, northern Laos - Peerapong Sritangsirikul; Sebastien Meffre; Khin Zaw; Ivan Belousov; Yi-Jen Lai; Alex Richards; Punya Charusiri (Journal of Asian Earth Sciences, 2024)

Geoenvironmental characterisation of legacy mine wastes from Tasmania – Environmental risks and opportunities for remediation and value recovery - Annah Moyo; Anita Parbhakar-Fox; Sebastien Meffre; David R. Cooke (Journal of Hazardous Materials, 2023)

Alkaline industrial wastes – Characteristics, environmental risks, and potential for mine waste management - Annah Moyo; Anita Parbhakar-Fox; Sebastien Meffre; David R. Cooke (Environmental Pollution, 2023)

Zircon U-Pb geochronology, Hf isotopes and geochemistry of intrusive rocks in the Simorgh prospecting area, Lut Block, eastern Iran: petrogenesis and geological implications - Reza Borabadi; Seyed Ahmad Mazaheri; Mohammad Hassan Karimpour; Sebastien Meffre; Jay Thompson; Rosanna Clare Murphy; Azam Entezariharsini (Geosciences Journal, 2018)

Compositional characteristics and geodynamic significance of late M iocene volcanic rocks associated with the C hah Z ard epithermal gold–silver deposit, southwest Y azd, I ran - Hossein Kouhestani; Majid Ghaderi; Mohammad Hashem Emami; Sebastien Meffre; Vadim Kamenetsky; Jocelyn McPhie; Khin Zaw; Rasoul Nasiri Bezenjani (Island Arc, 2018)
Whole‐rock geochemical and S r– N d isotopic data are presented for late M iocene volcanic rocks associated with the C hah Z ard epithermal A u– A g deposit in the U rumieh‐ D okhtar M agmatic A rc ( UDMA ), I ran, to investigate the magma source, petrogenesis and the geodynamic evolution of the study area. The C hah Z ard andesitic to rhyolitic volcanic rocks are characterized by significant L arge I on L ithophile E lement ( LILE ) and L ight R are E arth E lement ( LREE ) enrichment coupled with H igh F ield S trength E lement ( HFSE ) depletion. Our geochemical data indicate an adakitic‐like signature for the volcanic rocks (e.g. SiO 2 > 62 wt%, Al 2 O 3 > 15 wt%, MgO S r/ Y > 70, L a/ Y b > 35, Y b Y E u anomalies), distinguishing them from the other volcanic rocks of the UDMA . The C hah Z ard volcanic rocks have similar S r and N d isotopic compositions; the 87 S r/ 86 S r(i) ratios range from 0.704 902 to 0.705 093 and the ε Nd (i) values are from +2.33 to +2.70. However, the rhyolite porphyry represents the final stage of magmatism in the area and has a relatively high 87 S r/ 86 S r ratio (0.705 811). Our data suggest that the andesitic magmas are from a heterogeneous source and likely to result from partial melting of a metasomatized mantle wedge associated with a mixture of subducted oceanic crust and sediment. These melts subsequently underwent fractional crystallization along with minor amounts of crustal assimilation. Our study is consistent with the model that the volcanic host rocks to epithermal gold mineralization in the UDMA are genetically related to late M iocene N eo‐ T ethyan slab break‐off beneath C entral I ran.

Secular distribution of highly metalliferous black shales corresponds with peaks in past atmosphere oxygenation - Sean C. Johnson; Ross R. Large; Raymond M. Coveney; Karen D. Kelley; John F. Slack; Jeffrey A. Steadman; Daniel D. Gregory; Patrick J. Sack; Sebastien Meffre (Mineralium Deposita, 2017)

Age constraints on the hydrothermal history of the Prominent Hill iron oxide copper-gold deposit, South Australia - Bryan Bowden; Geoff Fraser; Garry J Davidson; Sebastien Meffre; Roger Skirrow; Stuart Bull; Jay Thompson (Mineralium Deposita, 2017)

Pb‐isotope compositions of the Tasik Chini volcanic‐hosted massive sulfide deposit, Central Belt of Peninsular Malaysia: Implication for source region and tectonic setting - Mohd Basril Iswadi Basori; Khin Zaw; Sebastien Meffre; Ross Raymond Large; Wan Fuad Wan Hassan (Island Arc, 2017)
Lead isotope data of sulfides and host volcanic rocks from the Bukit Botol and Bukit Ketaya deposits, the two representative deposits of the Tasik Chini volcanic‐hosted massive sulfide (VHMS) deposit, Central Belt of Peninsular Malaysia, are reported. Lead isotope compositions of the associated sulfide minerals and volcanic rocks from the Bukit Botol deposit exhibit homogeneous and less radiogenic values ( 206 Pb/ 204 Pb showing a range of composition from 18.14 to 18.20, 207 Pb/ 204 Pb between 15.52 and 15.59 and 208 Pb/ 204 Pb from 37.96 to 38.35). Similarly, the Pb isotopic compositions of the host volcanic rocks from the Bukit Ketaya deposit yielded a narrow range to those of the sulfide samples ( 206 Pb/ 204 Pb from 18.04 to 18.20, 207 Pb/ 204 Pb between 15.43 and 15.57 and 208 Pb/ 204 Pb of 37.96 to 38.30). The uniform Pb‐isotope compositions of the sulfides in the ore horizon and the host volcanic rocks from both deposits suggest a derivation from a similar source reservoir and mineralization processes. In the framework of the tectonic model for the Central Belt of Peninsular Malaysia, both deposits display a range of lead isotopic compositions originated from mixing of bulk crust/juvenile arc and minor mantle sources, which are typical for VHMS deposits in an island arc–back arc setting.

Geochemistry, geochronology, and tectonic setting of early Permian (~290 Ma) volcanic-hosted massive sulphide deposits of the Tasik Chini district, Peninsular Malaysia - Mohd Basril Iswadi Basori; Khin Zaw; Sebastien Meffre; Robert Ross Large (International Geology Review, 2016)

Postmagmatic magnetite–apatite assemblage in mafic intrusions: a case study of dolerite at Olympic Dam, South Australia - Olga B. Apukhtina; Vadim S. Kamenetsky; Kathy Ehrig; Maya B. Kamenetsky; Jocelyn McPhie; Roland Maas; Sebastien Meffre; Karsten Goemann; Thomas Rodemann; Nigel J. Cook; Cristiana L. Ciobanu (Contributions to Mineralogy and Petrology, 2016)

Vanadium-rich ruby and sapphire within Mogok Gemfield, Myanmar: implications for gem color and genesis - Khin Zaw; Lin Sutherland; Tzen-Fu Yui; Sebastien Meffre; Kyaw Thu (Mineralium Deposita, 2015)

Age and paragenesis of mineralisation at Coronation Hill uranium deposit, Northern Territory, Australia - Karin Orth; Sebastien Meffre; Garry Davidson (Mineralium Deposita, 2014)

The key role of mica during igneous concentration of tantalum - Aleksandr Stepanov; John A. Mavrogenes; Sebastien Meffre; Paul Davidson (Contributions to Mineralogy and Petrology, 2014)

Age and tectonic setting of the Bavanat Cu–Zn–Ag Besshi-type volcanogenic massive sulfide deposit, southern Iran - Fardin Mousivand; Ebrahim Rastad; Sebastien Meffre; Jan M. Peter; Mohammad Mohajjel; Khin Zaw; Mohammad Hashem Emami (Mineralium Deposita, 2012)

Geological setting and timing of the Chah Zard breccia-hosted epithermal gold–silver deposit in the Tethyan belt of Iran - Hossein Kouhestani; Majid Ghaderi; Khin Zaw; Sebastien Meffre; Mohammad Hashem Emami (Mineralium Deposita, 2012)

U–Pb geochronology and Pb isotope characteristics of the Chahgaz volcanogenic massive sulphide deposit, southern Iran - Fardin Mousivand; Ebrahim Rastad; Sebastien Meffre; Jan M. Peter; Mike Solomon; Khin Zaw (International Geology Review, 2011)

Revealing the continental margin of Gondwana: the Ordovician arc of the Cordón de Lila (northern Chile) - Udo Zimmermann; Hans Niemeyer; Sebastien Meffre (International Journal of Earth Sciences, 2010)

Evolution of calc-alkaline to alkaline magmatism through Carboniferous convergence to Permian transcurrent tectonics, western Chinese Tianshan - Bo Wang; Dominique Cluzel; Liangshu Shu; Michel Faure; Jacques Charvet; Yan Chen; Sebastien Meffre; Koen de Jong (International Journal of Earth Sciences, 2009)

Collision tectonics in the New Hebrides arc (Vanuatu) - Sebastien Meffre; Anthony J Crawford (Island Arc, 2001)
The New Hebrides island arc in Vanuatu has been significantly modified by collision with several major submarine ridges and plateaux. Bathymetric sections taken at intervals along the arc, perpendicular to the trench, show that prior to collision at 3 Ma the morphology was typical of modern intraoceanic island arcs. Collision has caused uplift of the trench and forearc (up to 6000 m), subsidence around the arc volcanic edifices (up to 2500 m), forming a large intra‐arc basin and uplift of the arc‐backarc transition (up to 2000 m). In the transition zone between collisional and non‐collisional sections of the arc, subsidence occurs in the forearc and uplift occurs around the arc volcanoes. Many of these characteristics are typical of collisions in other Western Pacific island arcs such as the Tonga–Kermadec and Izu–Bonin arcs. The pattern of uplift and subsidence has important implications for the tectonic history of the New Hebrides system. The morphology of the arc shows that collision of the West Torres Massif probably accounts for at least half the uplift. Arrival at 0.7 Ma of the West Torres Massif in the trench may have caused the slowing of subduction in the entire northern half of the arc and not just in the central segment as previously suggested. Re‐equilibration of the arc following collision probably masks any evidence of collision prior to 3 Ma. For example, the Efate re‐entrant, a large indentation in the arc immediately to the south of the collision zone, probably originated as a result of erosion during collision followed by subsidence after collision. The Vanuatu collision shows that the subduction of seamounts and ridges in an intraoceanic arc temporarily changes the arc morphology, allowing the development of angular unconformities and changing the pattern of sedimentation. This provides information which can be used to facilitate recognition of these events in ancient arc‐related sequences.